How Do They See Us?: UNHCR's Representations of Syrian Refugees in “Every Second Counts” Campaign - Khalid, Marah (AUC Knowledge Fountain, 2024)
Representation is not just an opinion; it is the recreation of realities, facts, and stories that encourage receivers, who are readers and viewers, to build perceptions of a certain topic, objects, events, and human beings. Studying the representation of refugees in the media, UN agencies, and International organizations' press releases, videos, and images has been the main focus for many scholars for decades. However, little is known about refugees' perspectives on visuals produced by UN agencies. This research tries to add to the few studies concerning the captured human object, refugees, perspective using Hall’s encoding/decoding model (Hall, 1997) to analyze representations encoded by UNHCR in the “Every Second Counts” fundraising campaign and decoded by Syrian refugees in Jordan. Therefore, qualitative methods such as in-depth interviews, semi-structured interviews, and discourse analysis were used to understand 1) The representations developed by UNHCR while using Syrian refugees' photos and videos in the campaign via Instagram, alongside the captions used to describe these visual elements, and 2) The perspectives of Syrian refugees living in Jordan and Jordanian professionals working in the humanitarian field about the campaign. This study found that 1) Syrian refugees were mostly represented by UNHCR as victims to motivate the audience to donate as this style enhances the feeling of guilt in the spectator, dependent individuals on UNHCR and the donations that will be paid, and individuals with limited agency and lower status, 2) The study interlocutors adopted different systems/approaches to evaluate how Syrian refugees were represented as Syrian interviewees embedded the victimhood approach because they saw themselves as powerless vulnorbale receivers of aid, while Jordanian professionals embedded the humanitarian savior logic because of their different positionalities, 3) It is crucial for Syrian refugees to be part of the making process of any visual materials to have a sense of autonomy, and 4) The continuous dehumanizing representation of Syrian refugees might increase the gap between refugees and the host community and reinforce stereotypes about refugees.